Efek Mediasi Keterikatan Karyawan pada Pengaruh Keadilan Distributif dan Prosedural Terhadap Keinginan Berpindah - Patricia Fiona Ngadiman, Edalmen, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2019)
This study aims to determine the effect of distributive justice and procedural justice on turnover intention with employee engagement as a mediating variable at PT. XYZ The sample used was 83 respondents with a sample selection method using saturated sampling techniques. The study was conducted quantitatively and used a questionnaire to collect data. The results of this study concluded that distributive justice and procedural justice had a positive effect on employee engagement. Distributive justice has a negative effect on turnover intention, but the effect of procedural justice on turnover intention is not significant. Employee engagement acts as a partial mediation in distributive justice relations to turnover intention and acts as a full mediator on the influence of procedural justice on turnover intention. The next finding is that employee engagement has a negative influence on the desire to.